Developing a local capability for the manufacture of activated carbon from agricultural waste (2009)
Commercial activated carbons are produced from bituminous and lignite coal The environmental impacts and potentially increasing cost of coal has encouraged the search for other alternatives in agricultural wastes. The objectives of this study were to develop process flow diagrams for the large scale production of activated carbon from three agricultural wastes namely coconut shells, oil-palm shells, and sugarcane bagasse as well as carrying out an economic evaluation to estimate the cost to manufacture these activated carbons.